The Influence of PAF Leadership, Experience, and Effectiveness of Audit Procedures on Audit Quality in Public Accounting Firms (PAFs) in Medan - Hasbullah, Firman; Susanto (PT Inovasi Pratama Internasional, 2025)
This study analyzes the influence of Public Accounting Firm (KAP) leadership, auditor experience, and audit procedure effectiveness on audit quality at KAP operating in Medan City. The benefits of this study are expected to provide empirical contributions to the development of professional audit practices in Indonesia, especially in improving audit quality by strengthening leadership, auditor training, and improving audit procedures. The formulation of the problems raised is as follows: (1) Does KAP leadership affect audit quality? (2) Does auditor experience affect audit quality? (3) Does the effectiveness of the audit procedure affect audit quality?. The method used in this study was a quantitative method with an explanatory approach. The research sample consists of auditors who work at KAP in Medan and have a minimum of two years of work experience. Data were collected using a closed questionnaire with a Likert scale and data analysis was performed using multiple linear regression. The results indicate that KAP leadership and audit procedure effectiveness have a positive and significant effect on audit quality, with a t-statistic value of 3.612 and a p value of 0.001 (<0.05). Audit Procedure Effectiveness (X3) also has a positive and significant effect on audit quality, with a t-statistic value of 2.789 and a p value of 0.007 (<0.05). However, auditor experience does not show a statistically significant effect, with a p value of 0.225 (>0.05). These results indicate that managerial roles and work procedure systems have a greater impact on audit success than individual auditor experience. This study recommends the importance of improving leadership quality and periodic evaluation of audit procedures as a strategy to improve audit quality in KAP